2001
DOI: 10.1001/jama.285.5.606
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Vaccines to Protect Against AIDS, Tuberculosis, and Malaria

Abstract: Given the scope of the worldwide health problems caused by the acquired immunodeficiency syndrome, tuberculosis, and malaria, it is imperative that vaccines be developed to prevent these infections. Recent advances in the understanding of these diseases suggest that T-lymphocyte-mediated immunity is important in containing these infections. The application of novel vaccine technologies for eliciting this type of immunity promises to provide successful vaccines for controlling the spread of these deadly infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…Alum elicits strong humoural immune responses primarily mediated by secreted antigen-specific antibodies [35,36], which are effective against diseases such as diphtheria, tetanus and hepatitis B, where neutralising antibodies to bacterial and viral antigens are required for protection [37]. In contrast, alum is a poor inducer of cell-mediated immune responses and is unsuitable for vaccines that require a strong cellular immune response [38].…”
Section: Alummentioning
confidence: 99%
“…Alum elicits strong humoural immune responses primarily mediated by secreted antigen-specific antibodies [35,36], which are effective against diseases such as diphtheria, tetanus and hepatitis B, where neutralising antibodies to bacterial and viral antigens are required for protection [37]. In contrast, alum is a poor inducer of cell-mediated immune responses and is unsuitable for vaccines that require a strong cellular immune response [38].…”
Section: Alummentioning
confidence: 99%
“…Also, we have shown that preexposure vaccines are best if they prevent infection (mechanism 1) rather than allow infection but reduce the probability of fast progression to disease (mechanism 2) or reduce the rate of progression of latently infections to disease (mechanism 3). Whether or not new TB vaccines will prevent infection from occurring is not known, but BCG is clearly not able to prevent infection, and vaccines currently in development will likely not be able to do so either (29). As new TB vaccines and other control strategies become available, their potential benefits to TB control efforts can be evaluated by mathematical modeling.…”
Section: Public Health Policy Implicationsmentioning
confidence: 99%
“…Subunit vaccines consisting of mycobacterial protein antigens represent a potential safe and specific tool for the prevention of tuberculosis. A potential limit of subunit vaccines is limited persistence in vivo, resulting in the inability to induce strong primary responses with longlived memory (18). However, it was recently shown that in mice previously immunized with BCG, memory CD4 ϩ T cells could be boosted by a protein antigen (3).…”
Section: Several Lines Of Evidence Indicate That Activation Of M Tubmentioning
confidence: 99%